Clinico-Epidemiological Study of Lateral Ankle Sprains in Patients Attending a Tertiary Care Centre in Nepal - Shrestha, Praphulla; Chalise, Pralhad Kumar; Mishra, Anil Kumar (Nepal Medical College Journal, 2025)
Lateral ankle sprains are the most common injuries among the general population and athletes. The rate of recurrence of these injuries and their progression to chronic ankle instability is common. The study was performed to study the clino-epidemiological aspects of lateral ankle sprains in a tertiary care setting. This type of study has not been studied to date in our patient cohort and the results of the study can help to draw important guidelines in diagnosis and treatment of these injuries. All skeletally mature patients of both sexes with lateral ankle sprains were taken into the study. Relevant history, clinical examination, areas of tenderness, and anterior drawer test in plantar flexion and neutral were performed. A radiographic evaluation of the patient was performed to rule out bony injury. The total number of patients was 86. These injuries were seen in 46.5% of overweight or obese patients. The most common mechanism of injury is twisting injury in 52 patients (60.5%), followed by road traffic accidents and sports injuries, with 10 patients (11.6%) in each. Most of the ankle sprains were grade I injuries (72 patients, 83.7%), while 12 (14.0%) were grade II, and 2 (2.3%) were grade III injuries. This study has provided a comprehensive clinical and epidemiological overview of lateral ankle sprains in tertiary care setting in Nepal. It has highlighted the need for patient education regarding ankle sprains.